2014
DOI: 10.1186/1471-2407-14-133
|View full text |Cite
|
Sign up to set email alerts
|

RAS mutations in early age leukaemia modulated by NQO1 rs1800566 (C609T) are associated with second-hand smoking exposures

Abstract: BackgroundDeregulation of the MAPK genes signalling caused by somatic mutations have been implied in leukaemia pathogenesis, including RAS mutation (RASmut) in acute myeloid leukaemia (AML), which has been associated with intra-uterine chemical exposures. A case-case study was conducted in order to explore maternal and child exposures to tobacco smoking associations with early age leukaemia (EAL).MethodsCovariables of reference were MLL rearrangements (MLL-r), RASmut and NQO1 rs1800566 (C609T). Samples from 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Mitomycin C has remained as the only quinone-containing alkylating agent approved by the Food and Drug Administration for lung cancer treatment. Despite the overwhelming evidence suggesting importance of both NQO1 and KRAS in the pathogenesis of cancers, we are aware of only a single study investigating possible associations between them [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitomycin C has remained as the only quinone-containing alkylating agent approved by the Food and Drug Administration for lung cancer treatment. Despite the overwhelming evidence suggesting importance of both NQO1 and KRAS in the pathogenesis of cancers, we are aware of only a single study investigating possible associations between them [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, possible associations between NQO1 expression and KRAS mutational status have been rarely investigated in the literature. As of February 2014, entering “KRAS” and “NQO1” into the PubMed database [ 13 ] returned only one relevant study that investigated modulation of RAS (rat sarcoma viral oncogene homolog) mutations by NQO1 [ 14 ]. Our objective was to sequence KRAS and compare expression of NQO1 as well as a panel of five clinically relevant proteins in 108 non-small cell lung carcinoma (NSCLC), the most common form of LC, patients with and without KRAS mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans showed that prenatal exposure to air pollutants influences fetal development [ 4 ] and increases the incidence of some diseases in postnatal life [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although former studies performed in hyperdiploid childhood leukaemia strongly indicate that RAS mut are secondary hits (Case et al , ; Davidsson et al , ), this might not be a general rule for childhood ALL. Recently, an increased risk of RAS mut was associated with maternal tobacco smoking during pregnancy [odds ratio (OR) 3·06, 95% confidence interval (CI), 1·03–9·07], and this risk was modulated by the NQO1 609CT polymorphism (OR, 4·24, 95% CI, 1·24–14·50) (Andrade et al , ).…”
mentioning
confidence: 99%